Remembering Hedley - Bell, Coral (Canberra Papers on Strategy and Defence, 2008)
Remembering Hedley commemorates the life of Hedley Bull (1932-85), a pivotal figure in the fields of international relations and strategic studies. Its publication coincides with the official opening on 6 August 2008 of the Hedley Bull Centre at The Australian National University in Canberra.